Exploratory study of limnological parameters during the cycle of tambaqui fingerlings - Figueiredo, Fabiano Moreira; Bomfim, Satia Costa; Lima, Renato Abreu; Pontes, Wesley Paulo; Pontuschka, Rute Bianchini; Hurtado, Fernanda Bay (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
As the world population’s exponential growth in food security is put at risk, fish farming is one of the economic and effective alternatives in the production of noble and high protein food. For the success the monitoring of the quality of the water during the cycle is fundamental. The present study aimed at the characterization of the limnological parameters in tambaqui nursery (Colosoma macropomum). The study was carried out in the fish farm of Valle del Rio Machado in Presidente Médici - RO, from August/2015 through Junhe/2016, at 08 collection points: water supply and nurseries. The results showed that the parameters such as pH (6.1 to 8.8), ammonia (0.0 to 1.5 mg.L-1), nitrite (0.0 to 0.2 mg.L-1) , turbidity (4.1 to 62.0), were in accordance with what was established by Resolution CONAMA 357/2005; the temperature (28.2 to 38.2 °C), transparency (18 to 70 cm), and alkalinity (10 to 141 mg.L-1) were within the recommended range for fish farming in the specialized literature; dissolved oxygen ranged from 0.8 to 5.2 mg.L-1, but most of the sampled points were below 5 mg.L-1, the electrical conductivity ranging from 51.9 to 178.2 μS.cm-1 above that established by Resolution 357/2005/CONAMA. According to the results, the nurseries with cascade supply, receiving the same management are directly affected and there is thus the need for reformulation of the system in fish farming, so that it remains with individual supply and drainage.